Evaluation of Temporal Distribution of Recurrent Cholera Outbreak in Zambia. - Nachimata Nambela; Obi Shambaba; Musso Munyeme (Recent Trends in Infectious Diseases, 2024)
Background: Cholera cases in Zambia have been observed over a period without understanding the epidemiological cycles. The aim of the study was to evaluate the temporal distribution of recurrent cholera outbreak in Zambia from 1977 to 2019. Methods: Cholera case records of both sex and all ages were retrospectively analyzed. The primary source documents were reviewed including infectious diseases line list, notifiable diseases reports, Health Impact Assessment, District Health Impact Assessments, surveillance reports, Out-Patient Department & In-Patient Department books, and rapid response meeting minutes at district, provincial and national level. Used Excel to enter data and Stata to analyze data. Results: Zambia experienced 4 major recurrent cholera outbreaks between 1977 and 2020. The cumulative estimated total cases during the period under review accounted for 106,713 cases. While the mortality cumulative total was 4,367 deaths translating into a case fatality rate of 4.1%. The peak frequency of an epidemic curve elucidated an average of 10-year cycle of periodicity for both epidemiological cycle, pattern and interval of occurrence. Conclusion: The key findings from this study have been the elucidation of the 10-year epidemiological cycle. This means that control measures can be developed using the observed cycle of periodicity, as part of an early warning system by policy makers.
Keywords: Cholera; Epidemic curve; Epidemiological cycles; case fatality rate; infectious diseases